2015
DOI: 10.1007/s11627-015-9707-8
|View full text |Cite
|
Sign up to set email alerts
|

Field performance evaluation and genetic integrity assessment in Argyranthemum ‘Yellow Empire’ plants recovered from cryopreserved shoot tips

Abstract: Field performance evaluation and genetic integrity assessment were conducted in Argyranthemum plants derived from cryopreserved shoot tips. Some variations in root formation and vegetative growth were found in the plants following cryopreservation, but morphologies of the leaves and flowers, and color, number and size of the flowers remained unchanged in the plants recovered from cryopreservation, compared with the control. Assessments of genetic integrity by the two molecular markers: inter simple sequence re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…However, there existed a few studies, in which field behavior of cryoderived plants differed from that of the control. Working on Argyranthemum, Zhang et al (2015) reported that root formation and plant growth were reduced in the cryo-derived plants grown in the greenhouse, produces more dependable results than those using only one marker (Wang et al 2014a(Wang et al , b, 2018. ISSR and AFLP did not detect any polymorphic bands in Solanum tuberosum plants cryopreserved by droplet-vitrification, encapsulation-vitrification and vitrification (Wang et al 2014b;Li et al 2017 (Ahuja et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there existed a few studies, in which field behavior of cryoderived plants differed from that of the control. Working on Argyranthemum, Zhang et al (2015) reported that root formation and plant growth were reduced in the cryo-derived plants grown in the greenhouse, produces more dependable results than those using only one marker (Wang et al 2014a(Wang et al , b, 2018. ISSR and AFLP did not detect any polymorphic bands in Solanum tuberosum plants cryopreserved by droplet-vitrification, encapsulation-vitrification and vitrification (Wang et al 2014b;Li et al 2017 (Ahuja et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Final published version can be accessed at https://doi.org/10.1007/s11240-020-01820-7 Post-prints are subject to Springer Nature re-use terms ISSR was performed as described by Zhang et al (2015). Eight primers were selected from candidate primers, based on the number of amplified fragments in the range 500-2000 base pairs.…”
Section: Issr Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It is also important to evaluate field performance and plant functions, but up to now, studies on these topics are rather limited. There are works on papaya clones (Kaity et al 2009(Kaity et al , 2013 and Argyranthemum in the reproductive growth phase (Zhang et al 2015). Those observations did not prove any adverse effects on morphology and plant biochemical activity in regenerants.…”
Section: Original Papermentioning
confidence: 90%